Model Pengawasan Pembiayaan di BMT Mujahidin Pontianak - Sari, Nurma (IAIN Salatiga, 2014)
This research uses descriptive analysis method which aims to 1) know anddescribe the system of distribution of the finance products at the BMTMujahidin in the fiscal year 20092011; 2) know and explain the financingimplementation at the BMT Mujahidin Pontianak in the fiscal year 20092011.Results of the study were: KSU BMT Mujahidin was the same as other Shariahfinancial institutions, namely the financing run through a series of proceduressystematically arranged in part involving the marketing, financing, andmanagers has been quite effective. The manager accepted the proposalsanalyzed them and if approved will sign it. Supervision of the financing was done in three categories, first by doing active field supervision; Second by doing administrative supervision starting from the time of the filing process by way of checking the completeness of requirements until the reimbursement; third by helping the customer to identify the problems that will arise as early as possible in case of trouble and the BMT Mujahidin will participate in finding a solution for the customer.